Age at menarche and cancer risk at adulthood - André O. Werneck; Manuel J. Coelho-; Camila S. Padilha; Enio R. V. Ronque; Edilson S. Cyrino; Célia L. Szwarcwald; Danilo R. Silva (Taylor & Francis Group, 2018)
Aim: The aim was to evaluate the association between age at menarche and cancer using a nationally representative sample of Brazilian women. Methods: Data from the Brazilian Health Survey (PNS), a nationally representative survey conducted in 2013 (n = 33,715 women; ≥18 years), were used. Information on cancer diagnosis, age at menarche and other co-variables (chronological age, educational status, skin colour, menopause, leisure-time physical activity and tobacco smoking) were collected via interview. Logistic regression models were used for aetiological analyses. Results: The prevalence of cancer diagnosis was greater among women with early age at menarche [2.6% (2.0-3.5%)] compared to on-time [1.6% (1.4-1.9%)] and late women [2.0% (1.1-3.4%)]. The onset of menarche ≤11 years was significantly associated with cancer risk, regardless of co-variables [OR =2.45 (1.34-4.48)], compared to the late group. Conclusion: Early age at menarche was associated with cancer risk in adulthood, regardless of race, educational status, chronological age, obesity, menopause onset, tobacco smoking or physical activity.